Development of Inquiry-Based Physics Learning Modules on Linear Motion Materials for Senior High School Students - Nur Arisa Arisa; Lukman Hakim; Lefudin Lefudin (Faculty of Science and Education, UIN Walisongo Semarang, 2022)
This study aims to produce valid, practical, and effective inquiry-based learning modules to improve students' understanding of the concept of rectilinear motion. This research uses the ADDIE model of Research and Development (RD). Data collection uses walkthroughs, questionnaires, and tests. The research subjects were students of class X MIPA 2 SMA Negeri 2 Babat Supat. Based on the data analysis, the learning modules developed were stated to be valid, practical, and effective. The results of the expert review obtained an average value of 87.5% which was categorized as very valid, one to one obtained an average value of 88% which was categorized as very practical, the small group obtained an average value of 89.8% which was categorized as very practical, and the field test was obtained the average value of the pre-test was 41.19, and the post-test was 79.04 with an average N-Gain value of 0.64 in the medium category.